Kajian Analisis Pengaruh Geometri Penampang terhadap Kecepatan Gerak Pelampung Kapasitas 100 kg - Dinny Indrian; Kurniawan Kurniawan; Sindydevia Rahayu (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2022)
The WHO report states 372,441 people die every year due to drowning. The curative effort to overcome drowning is by means of a float. Nearly drowning victims need speed of handling. Therefore, the development of the buoy is directed at increasing the velocity of the motion of the buoy. The purpose of this research is to find a relationship between the geometry of the buoy section with the optimum speed of motion. The completion methodology in this final project is literature study, problem identification (buoy volume calculation), buoy design and design parameters, buoy sensitivity study to 100 kg payload, checking ergonomic limits, computational fluid dynamics studies (CFD) and checking fluid flow velocity in buoys. . The result is the fluid flow velocity targeted at five cross-sectional shapes (rectangle, circle, ellipse, bullet, and comparator), namely 2.8 m / s has not been achieved. By all the step done, we concluded that each section has an unique characteristic. Some of them were recommended to study in next research.